The Problem of Religion and Terrorism: A Sociological Critique of Katekisas (Spit for God) by Farid Latif (A Sociological Critique Study) - Kaliki, Wulandari; Latupapua, Falantino Eryk; Somelok, Grace (Universitas Pattimura, 2022)
This research is qualitative as it involves the collection of descriptive data and information regarding the interaction process with the subject under investigation. This research seeks to delineate the issues surrounding religion and terrorism, while also appraising the merits and shortcomings of the theatrical script. The data in this study were acquired via reading and note-taking methodologies. This study employed data analysis methodologies including meticulous examination of the theater script, data description, interpretation, evaluation, and conclusion formulation as the ultimate outcome of the research. The research findings on the play manuscript KATEKISAS (Spit for God) by Farid Latif indicate that it addresses the social issues prevalent in community life. The primary societal concern addressed in this article is the relationship between religion and terrorism. In this manuscript, the author critiques several individuals who exploit God's name for personal gain. The book exhibits the following faults and merits: 1. Insufficient story coherence, 2. Inappropriate conversation writing style. The strengths include: The author has effectively resonated with readers by candidly addressing societal issues.